AN INTEGRATED EXERCISE APPROACH FOR SECONDARY LUMBAR SPINAL STENOSIS- A CASE REPORT (International Journal of Physiotherapy, 2017)
Background: Lumbar spinal stenosis (LSS) is a narrowing of the spinal canal that can produce low back pain, leg pain, and weakness. Many treatment approaches are used for its treatment. An integrated exercise approach has been employed in this case, and its effects pre and post treatment has been compared.Case Summary: A 48-year-old female presenting with a complaint of pain in the lower back region which was radiating to both lower limbs. She also had difficulty to perform household work like bending, sitting and standing. After taking medicine for two months, the patient didn't get any relief and then she comes in Physiotherapy OPD. After the complete physical examination and assessment, secondary lumbar spinal stenosis was diagnosed. The benefits of integrated exercise protocol on LSS were reported, and treatment protocol was planned according to the identified problem areas of the patient. An intervention of 21 days (20-40 minutes per day, five days per week for three weeks) was given to the patient and improvement was taken on baseline evaluation and 11th day and 22nd day of post-intervention.Outcome measures: The Oswestry Disability Questionnaire observed the recovery of the patient, Modified Schober Test, Numeric Pain Rating Scale, SLR and Slump test.Conclusion: Considerable improvement was seen in Pain intensity, neural flexibility, ROM and Quality of life after the rehabilitation. It was observed that the integrated exercise protocol has helped in improving the patient with LSS.